The hundred and one dalmatians - Smith, Dodie; Grahame Johnstone, Janet Grahame Johnstone, Anne (Mammoth London, 2000)
Pongo the dalmatian and his wife Missis undertake a daring expedition to rescue their fifteen puppies from the clutches of the vicious Cruella de Vil